Thai learners’ acquisition of L2 collocations: an interlanguage perspective - Kietnawin Sridhanyarat (Penerbit Universiti Kebangsaan Malaysia, 2018)
The emergence of second language (L2) collocation studies has grabbed the attention of a number of scholars. However, few empirical studies from an interlanguage perspective have addressed the issue of how learners acquire L2 collocations. The current study investigated what grammatical and lexical collocations posed difficulty to Thai EFL learners and whether learners of different proficiency levels exhibited the same order of acquisition. The study also attempted to explore whether task differences significantly affected the learners’ acquisition process. The participants were organized into a high proficiency group (N = 45) and a low proficiency group (N = 45). Receptive and productive tasks were devised to gauge the learners’ collocation knowledge. In the receptive task, the learners were encouraged to identify errors. In the productive task, they were asked to write a correct collocate required for a certain context. The results illustrated that almost all target collocations were difficult for both advanced and basic groups. Only verb-preposition collocations did not pose any considerable difficulty to the advanced participants. In terms of acquisition order, there were palpable differences between the two groups. It was also discovered that the different tasks administered exerted a profound effect on the learners’ order of collocation acquisition. The key findings are discussed in light of first language (L1) transfer, transfer of prior knowledge of a particular congruent collocation, familiarity with receptive tasks, and effects of both receptive and productive tasks. The findings suggest that teachers can teach students a group of words rather than individual words by utilizing meaningful materials oriented toward specific difficult collocations or receptive-productive integration tasks. Teachers can also encourage their students to practice using frequency-based collocations and dictionaries in English classes.